Subcutaneous Dirofilariasis in Nova Scotia - David JM Haldane; B Lynn Johnston; Noreen MG Walsh (Canadian Journal of Infectious Diseases)
A case of dirofilariasis in a 78-year-old woman from Nova Scotia is described along with the histological findings and the basis of identification of the parasite. The patient developed a subcutaneous nodule, which was excised. Dirofilaria ursi and ursi-like nematodes are a rare cause of subcutaneous nodules. This is the first time dirofilariasis has been diagnosed in an adult in Atlantic Canada.